Zoning groundwater potential recharge using remote sensing and GIS technique in the Red river delta plain. Issue 1 (January 2022) - Nhan, Pham Quy; Hung, Le Viet; Le, Tran Thanh; Le Khoa, Thi Van; Nhan, Dang Duc; Cuong, Tran Quoc
Abstract: The Red River delta plain is the second largest delta in Vietnam and is located in the North of the country with an area of 14, 860 km 2 and residing more than 22.5 million inhabitants. Groundwater is mainly exploited in Quaternary sedimentary aquifers with a total discharge of about 3 million m 3 /day. Some localities have shown signs of over-exploitation such as in Hanoi and in Nam Dinh, which may lead to related problems such as depletion, subsidence, saltwater intrusion, and water pollution. In order to be able to sustainably exploit groundwater, the groundwater potential recharge needs to be estimated. There have been many studies using different methods to estimate the groundwater recharge and to zone potential recharge. In the study area, there are several studies for groundwater recharge, but some are still uncertain because of using indirect methods, some are locally estimated in specific areas. Therefore, the objective of this study is to apply remote sensing and GIS to zone the groundwater potential recharge and its verification by using radioactive isotope 3 H analysis in the Red River delta plain. Various types of satellite images have been used and interpreted to detect the different thematic layers which concern the groundwater potential recharge. GIS has been applied as a platform for analysis and integration of thematic layers for zonation, finally. Field trip and water sampling for chemical and radioactive 3 H analysis were also conducted. Zones with low, moderate, and high groundwater potential recharge have been delineated with good agreement from the direct estimation of groundwater recharge by radioactive isotopes 3 H.